Goals, Trust, Participation, and Feedback: Linking Internal Management With Performance Outcomes. (17th October 2014) - Favero, Nathan; Meier, Kenneth J.; O'Toole, Laurence J.
Abstract : Much recent work in the study of public administration has emphasized new challenges and relatively unusual aspects of management. However, it is likely that the core features of traditional public administration play a crucial role, particularly regarding the delivery of performance. The most venerable of these aspects of public management have to do with "internal" management. We focus here on a cluster of key, intertwined management practices: setting challenging but feasible goals, building trust through credible commitments, encouraging employee participation, and providing feedback. We examine the relationship between such internal management at the mid-level, as perceived by subordinates rather than the managers themselves, and educational performance for more than 1, 100 schools in the New York City school system over a 3-year period. The results indicate that internal management matters, often sizably, for delivering educational outcomes. The findings are robust to autoregressive specifications and the purging of halo effects, and they hold across multiple performance measures. Managers' setting challenging goals appears to be especially important in generating educational results.